Kritik terhadap Pendekatan Konseling Feminis Berbasis Islam dalam Konteks Komunikasi dan Dakwah - Putriana, Haryani; Nurjannah (KOMUNIDA : Media Komunikasi dan Dakwah, 2023)
Feminism is known for the vision of fighting for equality for women; it is often seen as contradictory to the values ​​contained in religion. Counselling is a means of distribution by professionals to counselees with a feminist approach; it is something new and gets pros and cons responses. The purpose of this study is to provide criticism and contribution of ideas regarding feminist counselling and the Islamic religion, which is often claimed to be the carrier and has significantly contributed to women's shackles of the patriarchal system until now. This research will use the library study method; it will collect data through available sources both in the library and online media in the form of scientific articles. The result of the study showed there were Islamic religious values ​​that can be used as reference material when providing feminist counselling services, so that was not only referred to values ​​originating from the West, and Islam refutes feminist accusations.